Molecular analysis of environmental and human isolates of Salmonella typhi. - Thong, Kwai Lin; Cordano, A.M.; Yassin, R.M.; Pang, T. (American Society for Microbiology, 1996)
Molecular characterization of a total of 54 isolates of Salmonella typhi from Santiago, Chile, was performed by pulsed-field gel electrophoresis (PFGE) after digestion of chromosomal DNA with three restriction endonucleases: XbaI (5'-TCTAGA-3'), AvrII (5'-CCTAGG-3'), and SpeI (5'-ACTAGT-3'). Thirteen of the 54 isolates were obtained from environmental sources (sewage and river water), and the rest were isolates from clinical cases of typhoid fever. Considerable genetic diversity was detected among the human isolates obtained in 1994, as evidenced by the presence of 14 to 19 different PFGE patterns among 20 human isolates, with F (coefficient of similarity) values ranging from 0.69 to 1.0 (XbaI), 0.61 to 1.0 (AvrII), and 0.70 to 1.0 (SpeI). A total of eight phage types were detected among these 20 isolates, with 50% possessing the E1 or 46 phage type. There was no correlation between PFGE pattern and phage types. Similar diversity was seen among 21 isolates obtained in 1983, with 17 to 19 PFGE patterns detected and F values of 0.56 to 1.0 (XbaI), 0.55 to 1.0 (AvrII), and 0.67 to 1.0 (SpeI). Comparison of these two groups of human isolates obtained 11 years apart indicated that certain molecular types of S. typhi are shared and are able to persist for considerable periods. A similar degree of genetic diversity was also detected among the environmental isolates of S. typhi, for which 10 to 12 different PFGE patterns were detected among the 13 isolates analyzed, with F values ranging from 0.56 to 1.0 (XbaI), 0.52 to 1.0 (AvrII), and 0.69 to 1.0 (SpeI). Certain molecular types present among the environmental isolates of S. typhi were also found among the human isolates from the same time period, providing evidence for the epidemiological link between environmental reservoirs and human infection.